Koperasi Pesantren Bir Aly Sebagai Sarana Pemberdayaan Ekonomi (Studi Kasus Pondok Pesantren Robithotul Ulum Jatirejo Mojokerto) - Ashar, Salim (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2016)
Koperasi Pesantren Or abbreviated to Kopontren BIR ALY is one means learning for Robithotul Ulum boarding school students in order to foster an entrepreneurial spirit that is reliable in order to face the future life after they graduate from the school. As well as to foster independent spirit of entrepreneurship. In addition to being a place for moral development of students piety and learning Islamic sciences, pesantren should need also diversified specialty and featured scientific or practical expertise specific to diversify. That is, each boarding schools need to make the benefits (plus) certain that distinguish schools with each other pesantren, for example by increasing excellence in science expertise such as excellence expertise in the study of hadith, or discipline specific religion, or it could be in the form of practical skills other for example language skills, agricultural skills and other practical skills. The purpose of this study was to describe the role and functions of the Cooperative Pesantren Bir Aly As a Means Economic Empowerment in Robithotul Ulum Islamic Boarding Jatirejo Mojokerto. This study took place in the village of Jatirejo kec Jatirejo mojokerto kab. Jatirejo area known as agricultural areas, as well as many emerging companies and rock miners, many pesantren stand, a region still dominated rural areas. Economic development practices in boarding schools in order to sharpen practical skills for students, still need support from other parties to support, either from the government, private sector and society in general. Comparison between Turus and Pesantren Pesantren Baitul Hamdi in this case study is not intended as an effort to show which one is better, but rather as an attempt to describe variations in economic enterprise started piloted in boarding schools. Each has advantages and disadvantages that can be used as an ingredient to learn from each other. From this research, we can conclude several steps that can be done in the development of the economy in order to empower schools. Among the local authorities and the schools need to do (1) joint identification of potential schools and regional problems. Identification is required so that it develops economic activities in accordance with the carrying capacity of the environment; (2) establishing economic commodity that fits in a religious boarding school in accordance with the needs of the market that can be used to improve the common welfare; (3) develop a joint program that is based on empowerment schools, may be useful.